ACTIVATED CARBON FROM BAMBOO WASTE : EFFECT OF ACTIVATION SEQUENCES AND IRON-COBALT IMPREGNATION TO MATERIAL PROPERTIES AND CATALYST PERFORMACE - Jimmy, Jimmy; Roesyadi, Achmad; Suprapto, Suprapto; Kurniawansyah, Firman; Anggraini, Warih; Rahmawati, Rizka (Journal of Applied Engineering Science, 2020)
Bamboo “Ori” (Bambusa blumeana) is a potential raw material for activated carbon production due to rapid growth and abundant availability. Raschig ring activated carbon for industrial catalyst, catalyst support and adsorbent in purification process can be made from small diameter bamboo branches. The activated carbon as a support for Fe and Co catalysts in Fischer-Tropsch synthesis provides an opportunity for direct conversion from synthesis gas (CO and H2) to biofuel (C5-C19). The study emphasized on studying the effect of activation sequence on the activated carbon and impregnation product properties. Activated carbon, converted from bamboo waste through various activation sequences, was treated with steam, phosphoric acid and carbonization, followed by impregnation with 10% metal loading. Fe composition in the initial mixture was varied at 0-40% from total composition. After impregnation, reduction was applied by flowing hydrogen gas at 4000C for 10 hours. These catalysts were performed for Fischer-Tropsch synthesis in a batch reactors. The activation sequence of carbonization-acid and acid-carbonization gave identical surface area (2173 and 2091 m2/g), much greater than steam-carbonization-acid and steam-acid-carbonization (427 and 478 m2/g). Functionalization with nitric acid produced oxygen functional groups of carboxyl, carbonyl, alcohol and phenol. Catalyst reduction gave Fe, Co and Fe-Co alloys as active metal and little oxide of Fe2O3 and Co3O4. The larger amount of Fe-Co alloys were formed on 30Fe-70Co/Activated Carbon and 40Fe-60Co/Activated Carbon catalyst. Fischer-Tropsch synthesis in batch at H2/CO = 2, Fe-Co/activated carbon catalyst, 2500C, 8 bars for 18 hours. The n-paraffin compound is only formed in 40Fe-60Co/AC catalyst which contained the most Fe-Co alloys. The more Fe-Co alloys content was, more n-paraffin was formed. The n-paraffin (OH) compound was only formed in 10Fe-90Co/AC. The more Co content was, more n-paraffin (OH) was formed.
Keywords: iron-cobalt composition; functionalization; activated carbon; activation sequences; bamboo waste